Synchronized production and logistics via ubiquitous computing technology - Luo, Hao; Wang, Kai; Kong, Xiang T.R.; Lu, Shaoping; Qu, Ting (Robotics and computer-integrated manufacturing, 2017)
The integration of manufacturing and logistics has drawn widespread research attentions in recent years. This paper focuses on the Synchronized Production and Logistics (SPL), which is operational level integration. SPL　is defined as synchronizing the processing, moving and storing of raw material, WIP and finished product within one manufacturing unit by high level information sharing and joint scheduling to achieve synergic decision, execution and overall performance improvement. Through analysing the requirements and challenges in real life industry, the ubiquitous computing is adopted as an enabling technology and an Ubi-SPL (Synchronized Production and Logistics via Ubiquitous Technology) framework is proposed. This framework is consists of four layers, which creates a close decision-execution loop by linking the frontline real time data, user feedback and optimized decision together. A real life case study of applying Ubi-SPL solution in a chemical industry has been conducted. The implementation results show that the proposed Ubi-SPL solution can significantly improve the overall performance in both production and logistics service. •This paper focuses on the Synchronized Production and Logistics.•The ubiquitous computing is adopted as an enabling technology.•Synchronized Production & Logistics via Ubiquitous Technics framework is proposed.•A real life case study in a chemical industry has been conducted.